Óleo essencial de Eucalyptus staigeriana nanoencapsulado para utilização como conservante em alimentos - Herculano, Emanuele Duarte (2014)
In this study, the Eucalyptus staigeriana essential oil (ESO) was nanoencapsulated and determined the bactericidal effect of its active principle against two strains of pathogenic mircrorganisms, as a preliminary study for use in food preservation. The process occurred by forming a nanoemulsion and spray-drying, using the cashew gum (CG) as encapsulating material. The nanoparticles were characterized by analysis of particle size distribution, zeta potential, absorption spectroscopy in the infrared Fourier transform spectroscopy (FTIR), thermal analysis (TGA/DSC), in vitro release kinetics, gas chromatography coupled to mass spectrometry (GC-MS) and stability of the encapsulated. Was also determined the Minimum Bactericidal Concentration (MBC) of nanoparticles, essential oil, and cashew gum to evaluate its antimicrobial activity against Listeria monocytogenes ATCC 19115 (Gram-positive) and Salmonella Enteritidis IAL 1132 (Gram-negative). The nanoparticles had size ranging from 27.70 ± 3.42 nm to 432.67 ± 41.47 nm in accordance with the formulation, and negatively charged surface. The presence of ESO in the nanoparticles is observed through changes in peak resolutions of the spectra obtained by FT-IR. Thermal analysis showed the main events of mass loss of the samples associated with the degradation of CG. The content of ESO nanoencapsulated varied between 4.76% and 7.12%. The increase in the proportion of CG favored the rapid release of oil in water due to the increased hydrophilic character, and enhance the ability of the nanoparticles to retain the ESO in the polymeric shell during the 365 days. The results for MBC indicated a bactericidal action of the nanoencapsulated oil, and pure oil more efficient in Gram-positive. However, the nanoparticles showed better results against Gram-negative bacteria, due to a possible synergistic effect between the CG and ESO.